The Determinants Of Maternal Death Risk In Singosari, Malang Year 2015-2022 - Nur, Asvi Nisa (Jurnal Gizi dan Kesehatan Nusantara, 2024)
Maternal death occurs while in pregnancy, childbirth, and the 42 days after delivery or the postpartum period due to pregnancy or its care. This study aims to: 1. know the risk determinants that affect maternal mortality; 2. know whether there is an influence between pregnancy complications, delivery complications, postpartum complications, medical history, age, parity, pregnancy spacing, antenatal care, nutritional status, and anemia status on maternal mortality. Employing a case-control study design combined with an analytical observational research methodology 1: 2. Randomly chose the subjects and matched the control group with cases. The study’s group size is 48 people. The Chi-Square test was used to look at the relationship or effect of the independent factors on maternal mortality. The odds ratio was used to look at the risk of being exposed to the independent variable on maternal death in Singosari District, Malang Regency. The results are Age and parity did not affect the incidence of maternal death. Pregnancy complications have a 93 times risk. Comorbidities have a 24.1 times maternal death risk; pregnant women with a spacing of pregnancies have a risk of 15 times; pregnant women who have Chronic Energy Deficiency have a risk of maternal death by 4.2 times; and pregnant women with anemia have a risk of 5,4 times.